PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO ANIMASI KESELAMATAN KEBAKARAN PADA MATA PELAJARAN PENDIDIKAN JASMANI KELAS IX SMP BPS&K JAKARTA TIMUR - Nurfaridah, Mutiara Rida (Jurnal Pendidikan Teknik dan Vokasional, 2022)
Until now, fire disasters cannot be avoided, both in the industrial sector, housing and even in the forest. From various types of fire cases, it is very detrimental if there are casualties, so there is a need for education about fire safety learning for adults, teenagers and even children. Children's understanding of danger and self- protection causes children to be less able to anticipate and overcome dangerous conditions around themselves. This can usually be fatal for the safety of the child. Even when there is no adult supervision around the children, they cannot optimally look after and supervise the children. The results of the development of learning media for the feasibility of animated videos that cause fires and how to prevent fires, according to material experts, are categorized as feasible with a value of 76% measured by several aspects, namely: material coverage, presentation clarity, language aspects, understanding. Meanwhile, the feasibility of animated videos that cause fires and how to prevent fires, according to media experts, is categorized as very feasible with a score of 84% measured by several aspects, namely: text, images, video, audio, program effectiveness. And the feasibility of animated videos that cause fires and how to prevent fires based on the assessment of junior high school students is categorized as very feasible with a score of 88% measured by several aspects, namely: text, images, video, audio, program effectiveness.